2014 IEEE Fourth International Conference on Big Data and Cloud Computing 2014
DOI: 10.1109/bdcloud.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Use of Social Media in Natural Disasters: A Systematic Review

Abstract: Social media sites are playing a significant role in rapid propagation of information when disasters occur. This effective communication platform is a great useful tool for emergency (disaster) management agencies during all phases of disaster management life cycle: prevention (mitigation), preparedness, response, and recovery. This study has conducted a systematic review of social media use in disaster management literature to identify how social media sites have been used during these four critical phases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Disasters are complex in nature, which may have disproportionate effects at varying speed. Information exchange is pivotal during the disaster management processes (i.e., prevention, preparedness, response, and recovery), particularly in the response phase, as the dynamic and complex nature of the extreme natural disasters increases the rate of communication between stakeholders (Abedin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Disasters are complex in nature, which may have disproportionate effects at varying speed. Information exchange is pivotal during the disaster management processes (i.e., prevention, preparedness, response, and recovery), particularly in the response phase, as the dynamic and complex nature of the extreme natural disasters increases the rate of communication between stakeholders (Abedin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Social networks have been defined as ‘online venues for information sharing and social communication, where users create public profiles, interact with friends, and connect with other users’ (Masedu et al, , p. 1). Although social media is currently used in combination with traditional measures, during many recent extreme events it has actually been preeminent, broadcasting vital information before mainstream media (Murthy and Longwell, ; Cho et al, ; Abedin et al, ; Huang and Xiao, ; Takahashi et al, ). Furthermore, social media has become significantly instrumental in diminishing the communication gap between emergency services and individuals located in inaccessible areas during the aftermath of a disaster (Ehnis and Bunker, ; Cho et al, ; Neubaum et al, ; Takahashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Veil et al (2011) used the guidelines as a basis for a literature review and analysis which showed that "social media can be used to assist organizations in following best practices in risk and crisis communication" (Veil et al, 2011, p. 118). Abedin, Babar, and Abbasi (2014), conducting a literature review on social media for disaster relief, found that social media generally is considered an effective platform to create situational awareness among communities. Emergency responders can use social media to understand the sentiments of communities, and thus tailor crisis information to address the information needs and mitigate rumours.…”
Section: Using Social Media For Crisis Communicationmentioning
confidence: 99%